2009
DOI: 10.3390/molecules14114505
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Effects of Some Drugs on Immobilization Stress Combined with Cold Restraint Stress

Abstract: The aim of this work was to investigate the effect on antioxidant potential of some commonly used drugs (morphine, tramadol, bromocriptine, haloperidol and azithromycin) on immobilization stress (IS) combined with cold restraint stress (CRS) in the rat. After the drug treatment the animals were kept immobilized in the cold chamber at 4±0.3ºC for 3 hours and then decapitaed and the livers were extracted. The following parameters were determined in the liver homogenate: content of reduced glutathione, activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
1
14
0
3
Order By: Relevance
“…Şahin and Gümüşlü (2007) found CAT activities increased in the brain, liver, and heart. Popovic et al (2009) also found increased cerebral activity of CAT in immobilization and cold-induced stress. Kaushik and Kaur (2003) reported that CAT activity was decreased in the heart and liver due to cold stress.…”
Section: Discussionmentioning
confidence: 87%
“…Şahin and Gümüşlü (2007) found CAT activities increased in the brain, liver, and heart. Popovic et al (2009) also found increased cerebral activity of CAT in immobilization and cold-induced stress. Kaushik and Kaur (2003) reported that CAT activity was decreased in the heart and liver due to cold stress.…”
Section: Discussionmentioning
confidence: 87%
“…Tramadol is one of the synthetic opioids that has toxic effects at the cellular level by increasing LPO that can be used as a marker of the ROS-induced cell damages [48]. Moreover, it has been found that LPO is significantly increased in chronic heroin users [49].…”
Section: Discussionmentioning
confidence: 99%
“…The rats were housed 5 per cage under constant environmental conditions (20-24°C; 12 h light/dark cycle), and were given ad libitum access to standard pelleted food and water. After the administration of quail egg yolk and albumen extracts for 21 days, combined IS and cold-restraint stress (CRS) test was performed by immobilizing animals in the cold chamber at 4 ± 0.3°C; the plexiglass cage volume was adjusted to the size of the animal, to restrain completely their movements (Popovic et al 2009) for 2 h, except group 1. Group 2 animals were treated after stress with diazepam (5 and 10 mg/mL BW).…”
Section: Experimental Designmentioning
confidence: 99%
“…Cold and immobilization stressors can generate oxidative stress as well as skeletal muscle fatigue. Cold immobilization stress also called immobilization stress and cold-restraint stress had been described by Popovic et al (2009) as experimental induction of very extreme condition which cannot be carried out on human, but believed to have same effect on human as it revealed in animal models. Free radicals cause oxidative degradation of lipids, proteins, nucleic acids, and carbohydrates molecules thereby compromising cell integrity and function.…”
Section: Introductionmentioning
confidence: 99%